Bimbingan Kekayaan Intelektual Merek Jasa “Kelas 35” Paguyuban Batik Tulis Kebon Indah, Bayat, Klaten - Muafi Muafi; Rizqi Adhyka Kusumawati (Publikasi Indonesia, 2022)
The Kebon Indah Batik Tulis Society currently has a registered brand with the Ministry of Law and Human Rights since 2010 with the brand name